Heat and mass transfer performance of power-law nanofluid flow with thermal radiation and joule heating aspects: Surface heat flux analysis - Mhamed Benaissa; Zia Ullah; A. Dahshan; Md Mahbub Alam; Khadijah M. Abualnaja; Hanaa Abu-Zinadah; Abdullah A. Faqihi; Nidhal Ben Khedher (Case Studies in Thermal Engineering)
In the present advanced technological century, investigation of Joule-heat effects and radiating energy on power-law nanomaterial movement along a vertical extended sheet have presented the substantial potential in numerous engineering and technological applications. In this manuscript, the detailed numerical study of thermal-mass transmission with joule heating and thermal radiation influence on power-law nanofluid flow is presented. The physical problems are converted into a nonlinear ordinary differential equation under the implementation of similarity transformations, stream functions and Keller box method. Utilizing the similarity transformation, thermal energy, mass, and momentum are reduced to an algebraic system. Dimensionless stretching surface functions are impacted by nanofluid parameters such as magnetic parameter, thermophoresis parameter Nt, Nb, joule heating J, thermal radiation Nr, Le, and Pr. These effects are displayed numerically and graphically. With the use of MATLAB and Keller box method, the quantitative connection of skin friction and heat transport is demonstrated. The values of skin friction coefficient Cf, Sherwood number Shx and Nusselt number Nux are calculated in tables and compared with publish results for good harmony. It is found that higher value of joule factor enhances maximum heat-rate in fluid at n = 0.3.